ANALISIS DAMPAK PROGRAM BANTUAN SOSIAL KUBE TERHADAP PENDAPATAN DAN JAM KERJA DI KECAMATAN SUKASADA BULELENG - Rahameta, Ketut; Dewi, Putu Martini (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 10 No 8 (2021): VOL 10 NO 8, AGUSTUS 2021 [3104 - 3527], 2021)
Poverty incidents can change from time to time, the government makes efforts to overcome poverty problems through poverty reduction programs. The implementation of the program is basically aimed at improving the welfare of the community through increasing income and increasing the productivity of the community. The KUBE social assistance program provides opportunities for the poor to increase income and job opportunities in groups. The purpose of this study is to analyze: 1) the impact of the KUBE social assistance program on income levels in Sukasada District. 2) the impact of the KUBE social assistance program on the increase in working hours in Sukasada District. This research was conducted in Sukasada District, a sample of 63 respondents and the sampling technique was stratified random sampling. This study used a non-parametric test with the Mc Nemar method. Based on the results of research conducted, the average income of the community has increased after the implementation of the KUBE social assistance program and community working hours have increased after receiving the KUBE assistance program. Keywords: KUBE, Income, Working Hours.